2009
DOI: 10.1021/es803558r
|View full text |Cite
|
Sign up to set email alerts
|

Halogenated Contaminants in Farmed Salmon, Trout, Tilapia, Pangasius, and Shrimp

Abstract: Polychlorinated biphenyls (PCBs), polychlorinated dibenzo-p-dioxins and dibenzo-p-furans (PCDD/Fs), organochlorine pesticides (OCPs), polybrominated diphenyl ethers (PBDEs), hexabromocyclododecane diastereomers (HBCDs), and perfluorinated compounds (PFCs) were analyzed in popular farmed fish such as salmon, trout, tilapia, and pangasius and in farmed shrimp. The samples originated from southeast Asia, Europe, and South America. Results show the following: (i) Carnivorous species contained higher contaminant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 23 publications
4
76
1
Order By: Relevance
“…Berger et al 2009;Clarke et al 2010;Del Gobbo et al 2008;D'Hollander et al 2010a;Ericson et al 2008;Jogsten et al 2009;Mak et al 2009;Nania et al 2009;Ostertag et al 2009a;Tittlemier et al 2007;van Leeuwen et al 2009). Factors that could explain differences among studies could be geographical as well as temporal differences in use of PFC containing products, analytical methodology and sensitivity in the measurements of PFCs in food.…”
Section: Concentrations In Food and Beveragesmentioning
confidence: 99%
“…Berger et al 2009;Clarke et al 2010;Del Gobbo et al 2008;D'Hollander et al 2010a;Ericson et al 2008;Jogsten et al 2009;Mak et al 2009;Nania et al 2009;Ostertag et al 2009a;Tittlemier et al 2007;van Leeuwen et al 2009). Factors that could explain differences among studies could be geographical as well as temporal differences in use of PFC containing products, analytical methodology and sensitivity in the measurements of PFCs in food.…”
Section: Concentrations In Food and Beveragesmentioning
confidence: 99%
“…2011]) in 2009. PFOA and PFOS have previously been detected in various animal matrices (e.g., Fair et al 2010;Meyer et al 2009;O'Connell et al 2010;Schuetze et al 2010;Van Leeuwen et al 2009;Yeung et al 2009), and it therefore appeared possible that the consumption of wild boar meat could result in increased exposure of PFOA/PFOS in humans especially because PFCs have previously been detected in human matrices as the last link in diverse food chains (Haug et al 2009;Hoelzer et al 2009;Kärrman et al 2010;Wilhelm et al 2009;Zhang et al 2010).…”
mentioning
confidence: 99%
“…Independent European laboratories have also screened pangasius for various contaminants and found levels to be extremely low. One Dutch assessment found concentrations of a range of halogenated contaminants in pangasius to be lower than those in wild fish and trout and salmon farmed in the EU, with the latter species deemed responsible for (97%) human exposure to the sum of the contaminants investigated [35]. A separate Italian study reported the quality of samples analysed to be 'good', and well within the normal range found for fish sourced in Europe [36].…”
Section: Food Safetymentioning
confidence: 91%